Online Shopping Patronage: Do Demographics and Psychographics Really Matter? - Hou, Jianwei (Journal of Marketing Development and Competitiveness, 2020)
This study examines how consumer demographics and psychographics may influence their online shopping patronage (i.e., the frequency of online purchases). Findings show that younger people and individuals with a higher income and education level are likely to shop online more frequently, while gender has no effect on the frequency of online shopping. This study also finds that propensity to trust, variety seeking, and impulsive buying are positively related to the frequency of online shopping, while risk aversion is negatively related to the frequency of online shopping. Theoretical and managerial implications are discussed.